Serum Magnesium Level in Protein-Energy Malnourished Children - Warisha Ikhlaq, Adeel Khalid, Amber Kamran, Muhammad Rafique, Sharmeen Nasir, Rumana Sangi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Protein energy malnutrition (PEM) is mainly due to inadequate intake of food both in quantity and quality. Serum magnesium level can be detected to identify magnesium deficiency in malnourished children. Low magnesium level in these children is associated with illness and death. Objective: To determine the serum magnesium level in protein energy malnourished children who are under the age of 5 years. Study Design: Prospective Cross Sectional study. Setting: The Pediatric department, civil hospital, Karachi. Study period: From July to December 2021. Material and Methods: Total 245 patients of both genders with moderate and severe malnutrition were included. Venous samples were sent to laboratory and a centrifuge machine was used to separate the serum, which was maintained at a temperature of 20°C for serum magnesium test. Atomic Absorption Spectrophotometer was used to measure serum magnesium levels. Descriptive statistics were applied. Frequency and percentage was calculated. Stratification was done using chi square test and p-value ≤0.05 was considered as significant. Results: Total 156 male and 89 female patients were included in the study. Mean age was 26.63±15.17 months. Mean duration of malnutrition was 11.74±4.86 months. Mean mid upper arm circumference (MUAC) was 11.66±0.76 cm. Serum magnesium level was 1.78±0.22 mg/dl. Overall 180 (73.5%) have moderate PEM. Conclusion: Study showed low serum concentration of magnesium in children with PEM. Keywords: Serum Magnesium Level, Protein Energy Malnutrition, Children Under 5 Years.